Interleukin 10 Gene Promoter Polymorphisms in Patients with Chronic Periodontitis - Jumaa Abd-Alkareem , Suhad; Luaiby Atrooz , Ahmed; Dhia Hasan, Noor (Diyala Journal of Medicine, 2022)
Background: The anti-inflammatory cytokine, interleukin 10 (IL 10), has a crucial role in periodontal diseases. The gene coding for this cytokine is pleomorphic. In the promoter region of the IL 10 gene, two single nucleotide polymorphisms (SNPs), IL10 1082 and IL 819, have been discovered to affect IL 10 expressions. Objective: To investigate the association of two single nucleotide polymorphisms in the interleukin 10 gene (IL-10-1082 G/A and IL-10-819 C/T) with CPO. Patients and Methods: A total of 64 patients with chronic periodontitis (CPO) and another 40 apparently healthy individuals were enrolled in this case-control study. The IL-10 gene was amplified with two specific sets of primers. Genotyping was achieved by allele-specific polymerase chain reaction (AS-PCR). Results: The frequency of GG, GA and AA genotypes of the SNP IL-10-1082G/A among patients was 48.44%, 42.19% and 9.37% respectively, compared with 32.5%, 35% and 32.5% respectively, among controls. Logistic regression test revealed a significant difference in the frequency of AG (OR=0.19, 95%CI=0.06-0.62, P=0.006) and GG genotype (OR= 0.24, 95%CI=0.07-0.77, p=0.016) between patients and controls. Furthermore, the haplotype block GC (G allele of IL-10-1082G/A and C allele of IL-10-819 C/T) was more common in controls than patients (36.25% vs. 33.44%) with a significant difference (OR= 0.54, 95%CI= 0.29-0.99, p= 0.048). Conclusion: These data suggest that the IL-10-1082 G/A gene polymorphism could be a risk factor for CPO in Iraqi patients.